Lived Experiences of Technology and Livelihood Education Teachers on the Challenges and Benefits of Facilitating Online Learning - Evelyn Jaurigue-Sublay (JPAIR Institutional Research Journal)
This study aimed to describe the essence of the lived experiences of Technology and Livelihood Education Teachers on the challenges and benefits of facilitating online learning. This study utilized a qualitative method with a phenomenological perspective and a transcendental design. The result revealed three (3) superordinate themes with various subordinate themes for the ‘challenges’ of TLE teachers in facilitating online learning, which include: (1) Challenging Teaching Tasks; (2) Technological Infrastructure Availability and Management; and (3) Assessment and Monitoring of Student Learning. On the other hand, five (5) superordinate themes emerged under ‘benefits’ of facilitating online learning, including (1) Improvement of technical skills; (2) Improvement of communication skills; (3) Access to learning resources; (4) Fulfilling job; and (5) Learning convenience. This study suggested that teachers and students must have access to Information and Communications Technology (ICT) resources and facilities, both groups must receive adequate training, and curriculum materials must be digitized. Likewise, the school administrators may allocate more funds for the schools to have internal resources.  This is encouraged for the academic program to function.